CERMAT BERBAHASA INDONESIA SEBAGAI UPAYA MENINGKATKAN MUTU PENGGUNA BAHASA INDONESIA - Wahyono, Hari . (Majalah Transformatika, 2010)
Language is a tool Communication. Language has an important role as a. tool of communication. It is impossible for us to communicate without language. "Berbahasa Indonesialah dengan  Baik dan Benar" slogan has been announced by the government at 20 Mei 1998. The aim is of Indonesian language must be able to use as the standard of Indonesian Language. In order to be able to use standard Indonesian language we need to use it  carefully and accurately. Accuracy  in using  language  show quality  of using the language. The mistakes are usually accured when he or she doesnt have enough knowledge of the language rule. Key words: Indonesian Language, language rule, accuracy, quality